Strategi Manajemen Redaksi Infosumsel.Id Dalam Menghadapi Persaingan Media Online di Era New Media - Al Tasti, M. Aditya Thoriq; Syarifuddin, Achmad; Hamandia, Muhammad Randicha; Jannati, Zhila (An-Nadwah, 2023)
The rapid development of the internet has led to the proliferation of online media in Indonesia. This is becoming more and more competition between the online media. With so much competition between online media, this research was conducted to find out how the communication management strategy was carried out by Infosumsel Id as a new online media to overcome competition between other online media. The method used in this study is through a qualitative approach with the analysis of Henry Fayol's communication management theory, namely Functionalism Theory. Data collection techniques used are documentation studies, observations and in-depth interviews. The results of this study indicate that the management strategy implemented by Infosumsel Id has a good and effective communication foundation. Starting from the planning stage, Infosumsel Id takes steps to evaluate previous performance results and then maintain the good ones then replace the ineffective ones. At the organizing stage, Infosumsel Id uses a communication approach with the divisional team, then at the leading stage, the Editor in Chief of Infosumsel. Id really oversees the progress of each job in each division in the Infosumsel Id Editor so as not to deviate from their respective jobdesk, then at the actuating stage Infosumsel Id uses effective communication to move the division team, finally at the controlling stage the Infosumsel Editor in Chief Id supervises all articles to comply with company regulations. From the analysis of Functionalism theory it can be seen that the results of management strategy research by Infosumsel Id say that Planning, Organizing, Leading, Actuating and Controlling are important points in the communication management of a company. In addition, the editor-in-chief of Infosumsel Id also holds full responsibility for competing with competitor online media